Qualitative Analysen von Haushaltsstrategien und Entwicklungsrichtungen biologisch wirtschaftender Familienbetriebe in Österreich; Qualitative Analysis of Household Strategies and Developments of Austrian Family Farms engaged in Organic Agriculture - Manuela Larcher; Stefan Vogel (German Journal of Agricultural Economics (GJAE), 2010)
– Based on a dataset of a qualitative longitudinal study of two serial in-depth interviews of 74 Austria farming families engaged in organic farming, we analyse organic farming families household strategies for a growth of their farming operation change in agriculture. The results are discussed in light of the social science debate on farm development. Over the study period of 14 years the household strategies of 35 farming families led to professionalization in farming, while the household strategies of 18 families led to disengagement from farming. Eight farms showed a stable economic development and 13 an unsteady direction of farm development. Our results suggest, that professionalized farms are more likely survive economically. Whether professionalization in farming will continue depends on the importance of farming in the overall professional life of the families.
Keywords: 330; Ökologischer Landbau; Landwirtschaftlicher Familienbetrieb; Österreich